The Effect of Work Motivation and Work Environment on Employee Commitment and Satisfaction Work as a Mediation Variable (Study on BPJS Employment Office of Lhokseumawe and Medan Raya Branch Office) - Nina Fenina Siagian; Mesra B (International Journal of Management, Economic and Accounting, 2024)
This research delves into the intricate relationship between work motivation, employee commitment, and the work environment, examining how these elements intersect and influence organizational outcomes. The study proposes that employees who exhibit strong commitment are more inclined to harmonize their personal aspirations and goals with the overarching objectives of the organization, ultimately contributing to enhanced organizational stability and increased employee retention rates. Furthermore, the research investigates the crucial role of a positive and supportive work environment in nurturing positive employee emotions, such as job satisfaction and engagement, which in turn lead to improved work performance and productivity. Additionally, the study emphasizes the importance of effective leadership in cultivating a motivating work environment characterized by fair treatment, open and transparent communication channels, and genuine recognition of employee contributions.